Global research trends in music therapy for surgery: a bibliometric analysis (2009–2023) - Xiaoping Xu; Zhenglan Zhong; Yong Yi (Perioperative Medicine)
Abstract Music therapy, known for its profound impact on human emotions and physiology, has gained increasing attention for its applications in medical settings, particularly in surgery. This study conducted a bibliometric analysis of publications on the application of music therapy in surgery from 2009 to 2023, utilizing the Web of Science Core Collection (WoSCC) as the primary database. A total of 479 publications were analyzed using VOSviewer, CiteSpace, Microsoft Excel, and online bibliometric tools. Findings indicate a steady increase in annual publications since 2009, peaking in 2021. The USA leads global research efforts with 31.7% of publications, followed by China (17.7%) and Italy (10%). Harvard University was identified as the top contributing institution, while the Journal of Perianesthesia Nursing was the primary publishing journal, and the Cochrane Database of Systematic Reviews was the highest co-cited journal. Cao Hua contributed the most publications, and Nilsson U was identified as the most co-cited author (n = 131). Keyword analysis highlighted anxiety, therapy, music therapy, and pain as primary research trends. This study provides valuable insights into the evolving landscape of music therapy research in surgical contexts. Future efforts should focus on expanding interdisciplinary collaborations, exploring advanced technologies for personalized interventions, and investigating optimal implementation strategies to enhance the integration of music therapy into surgical practice.